Pelatihan Kewirausahaan dan Pemasaran Home Industry Melalui Media Digital Pada Paguyuban Sosial Marga Tionghoa Indonesia Cabang Tangerang - Gunawan, Indra; Kusnawan, Agus; Hernawan, Eso; Anggraeni, RR Dian; Hendra, Hendra; Purnama, Marselia; Andy, Andy; Sutandi, Sutandi; Susanti, Metta; Samara, Aldi; Hidayat, Adrian (LP3kM Universitas Buddhi Dharma, 2021)
The technological developments that are happening nowadays are growing rapidly. All aspects of human life in their activities use information technology as a tool to facilitate and accelerate activities carried out. On the other hand, competition in the economic sector is also getting tougher. All producers are competing in marketing their products to consumers. The era of information technology using internet networks makes the distortion of time and space meaningless. Marketing is an important aspect of economic activity. The combination of good marketing concepts with technology makes producers more reliable in maintaining their existence. The growth of Micro, Small and Medium Enterprises (MSMEs) is flourishing in Indonesia. According to data from the Central Bureau of Statistics (BPS) in 2016, MSMEs contributed 60.34% of Gross Domestic Product (GDP) and 89.2 percent of labor absorption. Many home industry MSMEs are growing and have a contribution to the economy. However, the contribution of MSMEs to the value of Indonesian exports has only reached 14.17% of the total exports. This data shows that the role of MSMEs in the Indonesian economy is very large. However, with the current development of information technology, it has not been optimized for business penetration through expanding marketing through digital media